Analysis of the relationship between cotton fiber quality and weather conditions in the southeast of Stavropol Territory - N. A. Khodzhaeva; L. P. Podolnaya (Труды по прикладной ботанике, генетике и селекции)
Background. Climate change leads to the worsening of cotton cultivation conditions in traditional cotton-producing countries, which, in its turn, can produce a positive impact on cotton cultivation in Russia. Assessment of the variability of fiber quality parameters in breeding lines and the effect of weather conditions in the east of Stavropol Territory will help to identify breeding trends and agricultural practices for this area.Materials and methods. The fiber produced in 2009, 2012, 2014, 2018 and 2019 by 30 breeding lines grown at Prikumskaya Experimental Breeding Station (Budennovsk, Stavropol Territory) was analyzed under the HVI system in Moscow and Kamyshyn. We compared the variability of fiber quality parameters by sampling over the years of research and conducted ANOVA and correlation analyses of the quality traits and temperature and rainfall indicators. Excel 2016 and Statistica 7 were used.Results and discussion. An analysis of the variability in individual fiber quality parameters showed that they reacted differently to changing weather; particularly sensitive were fiber strength and micronaire. A strong negative correlation was observed between these characters (r = –0.82), and they were most significantly affected by the temperature and precipitation in August. A hot and dry August contributed to the formation of fiber type 1–3, corresponding to the fiber of Egyptian cotton (Gossypium barbadense L.), in plants with habitus and earliness of G. hirsutum L. Under relatively cool and humid conditions of 2009 and 2012, the fiber of most lines was typical for the upland type. Knowledge of the relationship between fiber quality and weather conditions during the fiber development period will help to predict the quality of cotton fiber in advance and prognosticate its utilization.